The Effect of Consumer Motivation, Perception and Attitude on The Purchase Decision of Asus Brand Laptops (case study on students at Rusunawa II UNISMA) - Meri Kurniawati; Ridwan Basalamah; Eka Farida (Budapest International Research and Critics University, 2022)
Researchers conducted research on Asus brand laptop products because they saw increasingly sophisticated technology and Asus won the top position with a market share of 25.4%, in other words Asus laptop sales rose 11.3% compared to the previous year and were able to shift Acer as a vendor with biggest sales in Indonesia so researchers are interested in doing the research. This study aims to determine and analyze the influence partially and simultaneously from the motivations, perceptions and attitudes of consumers towards the purchase decision of Asus brand laptops for students in UNISMA Rusunawa II. The method used in this study is a multiple linear regression analysis method. The sample in this study is students who live in UNISMA Rusunawa II who use Asus brand laptops, amounting to 65 respondents from a population of 187 respondents. Data collection is done by distributing questionnaires. Analysis of the data used in this study used Validity, reliability, normality, multiple linear regression, multicollinearity, heterocedasticity, autocorrelation, F test and t test. The results of this study show partially and simultaneously on the variables of motivation, perception and attitude positive and significant effect on purchasing decisions. For the company should pay attention to the psychological side of consumers in terms of motivation, perceptions and attitudes of consumers, in order to increase and maintain the level of sales and increase purchasing decisions.